Frequência de fatores de risco cardiovascular em voluntários participantes de evento de educação em saúde - Coltro, Rodrigo Soler [UNESP]; Mizutani, Bruno Moreira [UNESP]; Mutti, Anibal [UNESP]; Barbieri Delia, Maria Paula [UNESP]; Baptista Martinelli, Luiz Mario [UNESP]; Cogni, Ana Lucia [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Associação Médica Brasileira, 2009)
INTRODUCTION. Cardiovascular diseases (CVD) are the main cause of death in Brazil.OBJECTIVE. To evaluate the frequency of CVD risk factors In a population attending a health education community event.METHODS. Retrospective study that included 428 completed forms with clinical and demographic information of volunteers attending a public event, in May, 2006. Data were expressed by means and standard deviation or proportions and compared by Student's t test or Chi-square test. Associations between Arterial Hypertension (AH), Diabetes Mellitus (DM) and clinical variables were analyzed by multinomial logistic regression. Significance level was p<0.05.RESULTS. Mean age was 57 +/- 14years, and women represented 58% of the total population. The main cardiovascular risk factors were AH (39.5%), DM (15.4%) and dyslipidemia (25.89%). The frequency of unawareness about these risk factors was respectively 8.4%, 17.5% and 33.1%.. Family history of CVD was reported by 41% while only 67% reported having any information about DM or dyslipidemia. Among obese individuals (IMC >= 30 Kg/m2, 27.3% of the population), systolic blood pressure (133 +/- 16mmHg), diastolic blood pressure (84 +/- 11.5mmHg) and casual glycemia (124 +/- 52.5mg/dl) were higher when compared to non-obese (p<0.05). There was a significant association between obesity and dyslipidemia (p=0.04). Age and IMC were independently associated with AH and DM.CONCLUSION. The high frequency of modifiable cardiovascular risk factors in this population suggests the need for educational programs to promote primary prevention, mainly for the elderly and overweight. [Rev Assoc Med Bras 2009; 55(5): 606-10]

INTRODUÇÃO: As doenças cardiovasculares (DCV) constituem a principal causa de óbito no Brasil. OBJETIVO: Avaliar a frequência dos fatores de risco para DCV em indivíduos participantes de evento de educação em saúde na comunidade. MÉTODOS: Foram analisados retrospectivamente 428 formulários contendo informações clínicas e demográficas de voluntários participantes de evento em saúde, realizado em maio de 2006. Comparações entre proporções foram realizadas pelo teste do Qui quadrado e entre grupos pelo teste t de Student. As associações entre hipertensão arterial (HAS) e diabetes mellitus (DM) e variáveis clínicas foram avaliadas pelo modelo de regressão logística multivariado. O nível de significância adotado foi p<0,05. RESULTADOS: A idade média foi 57±14 anos, sendo 58% mulheres. Os principais fatores de risco cardiovascular observados foram HAS (39,5%), DM (15,4%) e dislipidemia (25,8%), sendo que 8,4%, 17,5% e 33,1%, respectivamente, não sabiam informar sobre esses antecedentes. Antecedentes familiares de DCV ocorreram em 41% dos indivíduos e somente 67% referiram ter algum acesso a informações sobre DM ou dislipidemia. Entre os obesos (IMC>30 Kg/m2, 27,3% da casuística), a pressão arterial sistólica (133±16mmHg) e diastólica (84±11,5mmHg) e a glicemia casual (124±52,5mg/dl) foram maiores que nos não obesos (p<0,05). Houve associação entre obesidade e dislipidemia (p=0,04). Idade e IMC foram associados de forma independente com a presença de HAS e DM. CONCLUSÃO: A alta prevalência de fatores de risco modificáveis na população avaliada sugere a necessidade de medidas de saúde pública que promovam educação e prevenção primária dirigida, principalmente, para indivíduos idosos e com sobrepeso.
Cardiovascular risk factors in a population attending a community event on health education
Keywords: Diabetes mellitus; Obesity; Arterial hypertension; Risk factors; Community population